1999
DOI: 10.1038/sj.onc.1202712
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Sp1 and p300 in the induction of the CDK inhibitor p21WAF1/CIP1 during NGF-mediated neuronal differentiation

Abstract: Addition of nerve growth factor (NGF) to PC12 cells promotes neuronal di erentiation while inhibiting cell proliferation. In order to understand how NGF exerts its antimitogenic e ect during di erentiation, we have studied the mechanism by which this factor activates the promoter of the CDK inhibitor p21 WAF1/CIP1 . The minimal region of the p21 promoter required for the NGF-induction was mapped to a contiguous stretch of 10 bp located 83 bases upstream of the transcription initiation site. This GC-rich region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
2
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 57 publications
5
118
2
1
Order By: Relevance
“…A recent study which addressed the cooperation of Sp1 and p300 in the induction of the cyclin-dependent kinase inhibitor p21 WAF/CIP1 gene during nerve growth factor (NGF)-mediated neuronal differentiation showed that p300 and Sp1 associate in PC12 cells, and for this association of p300 and Sp1 on the promoter to be induced by NGF stimulation to likely form a transcriptional activation complex, consistent with results of cotransfection transcription assays (Billon et al 1999). Others have suggested that the progesterone receptor may act as a bridging factor to form a multiprotein complex containing Sp1 and p300 for the progesterone regulation of the p21 WAF/CIP1 promoter through Sp1-binding sites (Owen et al 1998).…”
Section: Biological Implications Of Interaction Of P300 and Sp1supporting
confidence: 52%
“…A recent study which addressed the cooperation of Sp1 and p300 in the induction of the cyclin-dependent kinase inhibitor p21 WAF/CIP1 gene during nerve growth factor (NGF)-mediated neuronal differentiation showed that p300 and Sp1 associate in PC12 cells, and for this association of p300 and Sp1 on the promoter to be induced by NGF stimulation to likely form a transcriptional activation complex, consistent with results of cotransfection transcription assays (Billon et al 1999). Others have suggested that the progesterone receptor may act as a bridging factor to form a multiprotein complex containing Sp1 and p300 for the progesterone regulation of the p21 WAF/CIP1 promoter through Sp1-binding sites (Owen et al 1998).…”
Section: Biological Implications Of Interaction Of P300 and Sp1supporting
confidence: 52%
“…Several important biological modifiers have been shown to activate p21 transcription through different Spl binding sites (Cartel and Tyner, 1999). For example, phorbol ester and okadaic acid induce p21 expression through Spl-1 and Spl-2 sites (Biggs et al, 1996), whereas the Spl-3 site in the promoter of p21 has been shown to be required for p21 induction by transforming growth factor-b, histone deacetylase inhibitors such as TSA and butyrate, lovastatin, nerve growth factor (NGF) as well as calcium (Datto et al, 1995;Nakano et al, 1997;Prowse et al, 1997;Sowa et al, 1997;Lee et al, 1998;Billon et al, 1999). In this report, we demonstrated that Spl-3 and Spl-4 in the promoter of human p21 gene are required for vinorelbinemediated transcriptional restoration of p21 in the p21-deficient Al cells, which may provide a new mechanism in drug-mediated p21 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The standard deviations from three independent experiments were shown 1997; Sowa et al, 1997). Interestingly, the region containing the responsive elements for HDAC inhibitors also mediates p21 transcriptional activation regulated by TGF-b (Datto et al, 1995), the protein kinase C activator phorbol esters (Biggs et al, 1996), the phosphatases 1 and 2A inhibitor okadaic acid (Biggs et al, 1996), the geranylgeranyltransferase I inhibitor GGTI-298 (Adnane et al, 1998), progesterone (Owen et al, 1998), and nerve growth factor (Billon et al, 1999). We have then demonstrated that Sp1 and Sp3 transcription factors bind speci®cally to the Sp1-3 site of the p21 promoter, the primary SAHA-responsive element.…”
Section: Discussionmentioning
confidence: 99%